Effects of Long-Term Airport Noise Exposure on Inflammation and Intestinal Flora and Their Metabolites in Mice - Jian Yang; Longwei Wei; Yuan Xia; Junyi Wang; Yan Bai; Yun Xia (Metabolites)
Background: The World Health Organization has indicated that airport noise is strongly associated with cardiovascular disease, with vascular inflammation identified as the primary mechanism. Therefore, long-term exposure to airport noise is considered far more harmful than other types of noise. However, there remains a lack of research into the mechanisms underlying long-term exposure to airport noise and harm to the human body. Methods: A mouse model was established and exposed to airport noise at a maximum sound pressure level of 95 dB(A) and an equivalent continuous sound pressure level of 72 dB(A) for 12 h per day over a period of 100 days. Quantitative polymerase chain reaction (qPCR) was used to detect the mRNA expression levels of pro-inflammatory and anti-inflammatory factors. Enzyme-linked immunosorbent assay (ELISA) was used to detect LPS, LTA, TMA, and TMAO levels. Intestinal flora composition was analyzed by 16S rDNA sequencing, and targeted metabolomics was employed to determine the levels of serum short-chain fatty acids. Results: Long-term airport noise exposure significantly increased systolic blood pressure, diastolic blood pressure, and mean blood pressure (p < 0.05); significantly increased the mRNA expression levels of oxidative stress parameters (nuclear matrix protein 2, 3-nitrotyrosine, and monocyte chemoattractant protein-1) (p < 0.05); significantly increased pro-inflammatory factors (interleukin 6 and tumor necrosis factor alpha) (p < 0.05); significantly decreased the mRNA expression level of anti-inflammatory factor interleukin 10 (p < 0.05); and significantly increased the content of LPS and LTA (p < 0.05). The composition of the main flora in the intestinal tract was structurally disordered, and there were significant differences between the noise-exposed and control groups at the levels of the phylum, family, and genus of bacteria. β-diversity of the principal component analysis diagrams was clearly distinguished. Compared with those of the control group, TMA-producing bacteria and levels of TMA and TMAO were significantly reduced, and the serum ethanoic acid and propanoic acid levels of the noise-exposed group were significantly decreased (p < 0.05). Conclusions: Long-term airport noise exposure causes significant elevation of blood pressure and structural disruption in the composition of the intestinal flora in mice, leading to elevated levels of oxidative stress and inflammation, resulting in metabolic disorders that lead to significant changes in the production of metabolites.